Abdominal aorta surgical intervention and acute renal injury - N. I. Glushkov; M. A. Ivanov; K. V. Samko; P. D. Puzdriak; P. B. Bondarenko; K. V. Zhdanovich; K. A. Petrova; I. A. Kolchinsky; N. Yu. Ponikarova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of this scientific research was to study risk factors, frequency and consequences of acute kidney injury (AKI) after open surgery on the abdominal aorta.METHODS AND MATERIALS. Outcome of surgical interventions in 65 patients were analyzed. AKI was detected in 11 of them; in rest 54 cases, AKI was not registered. The features of the perioperative period, kidney injury markers (creatinine, diuresis, urine), and the comorbidity were evaluated.RESULTS. The initial changes in renal activity, the emergency of intervention, hemodynamic instability, especially after more than 1000 ml perioperative blood loss, the presence of operations for multilevel peripheral arterial disease (MPAD) negatively affected on the AKI occurrence.CONCLUSION. Post-surgical AKI after infrarenal aortic interventions were observed more often in patients with previous kidney insufficiency, as well as after emergency interventions, in cases of hemodynamic instability.